Basic English - Lachance, Julie (McGraw-Hill Contemporary Learning, 2019)
Learn how to read and speak English with this easy-to-use workbook. Dozens of manageable, bite-sized lessons take you through the basics of the English language. Three-page units cover each subject, which can be completed in just 20 minutes. Each lesson covers a single grammar concept and is supported by many clear examples. The book includes tons of exercises help you practice your new language skills. Plus, you’ll also have access to streaming audio recordings of the most difficult English sounds to pronounce.